Mutagenicity and safety evaluation of Ashwagandha (Withania somnifera) root aqueous extract in different models - P. Kalaivani; R. Siva; V. Gayathri; Deepak Langade (Toxicology Reports, 2024)
Withania somnifera (Ashwagandha) also called as Indian ginseng, a revered herb from Indian traditional system of medicine is a rejuvenator and tonic (Rasayana) used for its varied benefits. The roots of ashwagandha exhibit properties like anti-inflammatory, aphrodisiac, anthelmintic, astringent, diuretic, stimulant and thermogenic. However, data of ashwagandha on its mutagenic effects are lacking. In the present study, in-vitro genotoxicity tests were used to evaluate the mutagenic potential of Ashwagandha Root Extract (ARE). Concentrations of 0.156 to 5.00 mg/plate ARE were used for conducting Bacterial reverse mutation test (BRMT). For chromosome aberration (CA) test ARE was used in concentrations of 0.25 to 2.00 mg/ml, and for micronucleus (MN) tests ARE concentrations of 500/1000/2000 mg/kg were used. Acute oral toxicity was conducted in Wistar rats (n = 25) as per the OECD guideline (#423) with doses of 500/1000/2000 mg/kg body weight in male Swiss albino mice for morbidity and mortality for 3 days. The BRMT and CA tests were conducted with and without metabolic activation (S9). The study was approved by the institutional ethics committee (IEC) and institutional animal ethics committee (IAEC). ARE failed to show any mutagenic effects up to a dose of 5 mg/plate in BRMT. Also, ARE did not show any clastogenic activity in doses up to 2 mg/ml in CA test and in micronucleus test up to 2000 mg/kg body weight. These results were observed with and without metabolic activation (S9) under the stated experimental conditions. No mortality, morbidity, or any clinical signs were observed up to 3 days following ARE administration. Ashwagandha root extract failed to show any mortality in doses up to 2000 mg/kg oral dosage and did not show any mutagenic (genotoxic) effects in high concentrations.